Understanding property law - Murphy, Tim (Understanding law, 2004)
"Understanding Property Law provides the background to an area of law that is notoriously inaccessible. Developed piecemeal by lawyers over centuries, the modern law is expressed in language that owes much to objectives and problems from a forgotten past. Standing back from their subject, the authors of this book elucidate how the practices of the past have shaped the development and form of the modern law. In doing so, they stress the role of lawyers as conveyancers in the transactions - such as sale, gift and inheritance - with which their clients become involved. The cultures within which these transactions were realised, and the meanings of these transactions for the lawyers involved, are examined here through direct reference to classic practitioner texts." "This new edition has been extensively revised and updated. Notably, it includes such recent legislative developments as the Land Registration Act 2002. Authoritative and clearly written, Understanding Property Law is an essential introductory text for new law students as well as for readers who wish to understand the context in which property law operates."--BOOK JACKET